Analisis Korelasi Faktor Resiko Kematian Di Ruang Isolasi Covid-19 - Hirdes Harlan Yuanto; Rudiyanto; Ida Sri Surani Wiji Astuti (PROFESSIONAL HEALTH JOURNAL, 2021)
Health workers and various other sectors are currently busy with handling world health cases of the Sars Cov-2 virus pandemic. The transmission of COVID-19 is very easy and dangerous, which is the cause of the increasing number of deaths. The large percentage of mortality rates for COVID-19 sufferers can be caused by internal factors and external factors. The purpose of this study was to analyze various factors that caused the death of COVID-19 sufferers. This scientific report uses observational analytics with a retrospective study design. The research target of Covid-19 patients in the isolation room of the Graha Medika hospital in August - December 2020 was 437 respondents. The research sample amounted to 305 respondents who were selected with simple random sampling technique. The instruments that the researchers used in data collection were writing instruments and medical records of patients in the COVID-19 isolation room. Most of the respondents were female, namely 161 respondents (52.8%), Almost half of the respondents aged >60 years, namely 119 respondents (39%), Almost all respondents underwent treatment for 1-5 days, namely 251 respondents (82.3% ), and most of the respondents had comorbidities, namely 228 respondents (74.8%). Factors of age, sex, comorbidities, had a statistical value (p<0.05) while the length of treatment was not related to the value (p>0.05). The most comorbid disease experienced by respondents was diabetes mellitus, and contributed to the death rate of 72 respondents (23.6%). Immediate handling and appropriate intervention for elderly COVID-19 sufferers of various genders and especially those with comorbidities to minimize the mortality rate of COVID-19 sufferers.